Pirfenidone inhibits fibrosis in foreign body reaction after glaucoma drainage device implantation - Jung KI; Park CK (Dove Medical Press, 2016)
Kyoung In Jung, Chan Kee ParkDepartment of Ophthalmology and Visual Science, Seoul St Mary’s Hospital, College of Medicine, The Catholic University of Korea, Seoul, South KoreaBackground: The aim of this study was to investigate the antiscarring effects of pirfenidone on foreign body reaction in a rabbit model of glaucoma drainage implant surgery.Methods: Adult New Zealand White rabbits had glaucoma drainage device implantation using Model FP8 Ahmed glaucoma valves. One eye was randomly assigned to receive postoperative intrableb injection of pirfenidone followed by topical treatment. The other eye underwent the same procedure but without the addition of pirfenidone. Histochemical staining and immunohistochemistry for blebs were performed.Results: The degree of cellularity was smaller in the pirfenidone group than in the control group at 2 weeks post operation (P=0.005). A few foreign body giant cells were detected in the inner border of the capsule, and their numbers were similar in the control and pirfenidone groups (P>0.05). Using Masson’s trichrome stain, the inner collagen-rich layer was found to be thinner in the pirfenidone group than the control group at 4 weeks (P=0.031) and 8 weeks (P=0.022) post operation. The percentage of proliferating cell nuclear antigen-positive cells was lower in the pirfenidone group than in the control group at 2 weeks post operation (total bleb, P=0.022; inner bleb, P=0.036). Pirfenidone treatment decreased the immunoreactivity of connective tissue growth factor at 2 weeks post operation (total bleb, P=0.029; inner bleb, P=0.018). The height and area of α-smooth muscle actin expression were lower in the pirfenidone group than the control group at 2 weeks, 4 weeks, and 8 weeks post operation (all P<0.05).Conclusion: Postoperative intrableb injection of pirfenidone followed by topical administration reduced fibrosis following glaucoma drainage device implantation. These findings suggest that pirfenidone may function as an antiscarring treatment in foreign body reaction after tube-shunt surgery.Keywords: fibrosis, bleb, glaucoma drainage device surgery, transforming growth factor-β